(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Burn injuries are a public health problem in developing countries like India specially in females. Fire can be considered as double edged sword. Our objective of the present study is to know the pattern of deaths due to burns, socio etiological factors involved and to suggest preventive measures. A prospective study based on autopsies conducted in R.N.T. Medical college, Udaipur (from 1 march 2018 to 30 September 2018) where total 780 Medico-legal autopsies were conducted during this period, out of those 86 were due to burn. 45 were male and 41 were females. maximum 46 of the cases were in the 21-40 years of the age group in both gender. Most of the cases were found to be from rural area (80.23%). Most common manner of burn was accidental (74.41%) followed by suicidal burns (22.09%). Majority of victims died as a result of flame burns (74.41%) and death due flame, major cases were females (62.5%). Majority of victims (41.86%) died with more than 80% burns and (52.32%) victims could not survive for more than 24 hours. The cause of death in (52.32%) cases was shock followed by septicemia in (32.5%).